2022
DOI: 10.7759/cureus.22247
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Secondary Spontaneous Pneumomediastinum and Pneumothorax in Severe COVID-19 Pneumonia

Abstract: IntroductionPneumomediastinum and pneumothorax are uncommon complications in COVID-19 patients. The exact prevalence, etiology, and outcomes are not well known. We report a case series of patients in our institution with COVID-19 related pneumomediastinum and pneumothorax and address these questions. MethodsWe conducted a single-center retrospective chart review of patients admitted at our institution with a positive polymerase chain reaction (PCR) confirming the diagnosis of COVID-19. A cohort of 500 potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Manna et al reported in their case that patients developed subcutaneous emphysema on average 13.3 days following the onset of symptoms [ 2 ]. Staiano et al reported an average of 10.75 days until the development of complications such as SPM [ 8 ]. In our case, the patient developed such complications approximately 10 days after the onset of her symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Manna et al reported in their case that patients developed subcutaneous emphysema on average 13.3 days following the onset of symptoms [ 2 ]. Staiano et al reported an average of 10.75 days until the development of complications such as SPM [ 8 ]. In our case, the patient developed such complications approximately 10 days after the onset of her symptoms.…”
Section: Discussionmentioning
confidence: 99%